Preliminary Validation of the Italian Night Eating Questionnaire (I-NEQ-16): Item Analysis and Factor Structure - Innamorati, Marco; Imperatori, Claudio; Lester, David; Fabbricatore, Mariantonietta; Gaudini, Lavinia; Contardi, Anna; Balsamo, Michela (Frontiers in Psychology, 2018)
Night eating syndrome (NES) severity is usually assessed with the Night Eating Questionnaire (NEQ). Although the most common version of the NEQ is composed of 14 items (NEQ-14), two additional items measuring distress associated with the night eating have been proposed, but they have never been included in past psychometric studies. The aim of the present study was to create an Italian version of the NEQ-16 (I-NEQ-16), with the inclusion of the proposed items for assessing the distress associated with night eating. A major objective of the study was to propose a unidimensional version of the I-NEQ-16 and investigate its psychometric properties. 482 Italian adults (380 women and 102 men; mean age = 25.5, SD = 10.9 years old) were administered the Italian versions of the NEQ, the Night Eating Diagnostic Questionnaire (NEDQ), and questionnaires measuring binge eating, emotional and external eating, diurnal chronotype, insomnia, and anxiety and depression severity. In order to improve unidimensionality of the I-NEQ-16, we removed from further analyses items 1, 4, and 7, because they increased the heterogeneity of the measure. Confirmatory factor analysis, indicated the fit of a modified one-factor model, allowing correlated errors between three pairs of items. I-NEQ-16 scores were significantly associated with all concurrent questionnaire scores and were able to categorize individuals according to their diagnosis of NES according to the NEDQ. Thus, the I-NEQ-16 is a valid measure that is potentially useful for investigating correlates of night eating in the general population.